Association Between Clinical Competencies and Mental Health Symptoms Among Frontline Medical Staff During the COVID-19 Outbreak: A Cross-Sectional Study - Chang, Qing; Su, Han; Xia, Yang; Gao, Shanyan; Zhang, Ming; Ma, Xiaoyu; Liu, Yashu; Zhao, Yuhong (Frontiers in Psychiatry, 2022)
Background: In China, mental health of frontline medical staff might be influenced by clinicians’ ability to handle the outbreak of coronavirus disease 2019 (COVID-19). Few studies to-date have addressed the association between clinicians’ competencies and mental health in this context. This cross-sectional study was to examine the prevalence of mental health symptoms among frontline medical staff handling the COVID-19 outbreak, and explore the associations between their competencies, and separate and concurrent depressive and anxiety symptoms. Methods: A total of 623 frontline medical staff were included in this study. Competencies, depressive symptoms, and anxiety symptoms were assessed using the short form of the Chinese clinical physicians’ competency model, Patient Health Questionnaire-9, and Generalized Anxiety Disorder-7 questionnaire, respectively. Logistic regression models were used to estimate the associations between one SD increase in competency scores and the prevalence of mental health problems. Results: The prevalence of depressive, anxiety, and comorbid depressive and anxiety symptoms was 40.93%, 31.78%, and 26.00%, respectively. Among the medical staff with higher total competency scores, the prevalence of depressive (odds ratios (ORs) = 0.67, 95% confidence intervals (CIs): 0.55-0.81), anxiety (OR = 0.68, 95% CI: 0.56-0.83), and comorbid anxiety and depressive symptoms (OR = 0.69, 95% CI: 0.55-0.83) was lower than among their lower-scoring counterparts. Subgroup analyses stratified by core competency scores revealed similar associations as the main analyses. Conclusion: The present findings highlight the association between high core competency scores and lower prevalence of depressive, anxiety, and comorbid anxiety and depressive symptoms.